INTERPRETASI POLA ALIRAN FLUIDA PANAS BUMI DENGAN METODE SPONTANEOUS-POTENTIAL (SP) DAN SUHU PERMUKAAN DANGKAL DI LERENG UTARA GUNUNG TELOMOYO KABUPATEN SEMARANG - Maila Shofa; Udi Harmoko; Sugeng Widada (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
The model heat flow at Telomoyo Mountain Semarang District has measured and identified using spontaneous potensial and shallow temperature surface methods.Field data has proceed using Microsoft Excel which the result entered to Surfer11 with the result map contour of SP and temperature distribution. The result showed that range anomaly SP about -40mV-70mV and distribution of temperature which has temperature range 23,5º-31ºC. The direction of heat flow direct from South to North-East.Key Words : Spontaneous-potential, shallow temperature surface, Sufer11, Model Heat Flow, Telomoyo Mountain